2020
DOI: 10.1176/appi.ps.201900624
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a Parenting Program for Transnationally Separated Chinese Immigrant Families: Community-Based Pilot Program

Abstract: Children who experience transnational separation (TS) from their parents, often referred to as "satellite babies," endure a relatively common but underdiscussed experience. To date, no evaluations of clinical interventions to specifically support transnationally separated families have been described. This column describes implementation of a group therapy pilot program for parents to address parenting and emotional concerns related to TS at a social services agency in Boston's Chinatown. Parent and therapist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Parent group sessions indicated that parents did not realize that they should show or tell children that they love them and the impact of not doing so before they attended the program. Previous studies have shown that neglect, especially emotional neglect, is among the most prevalent types of child maltreatment in China (Wang, Cheng, et al, 2020; Wang, Wong, et al, 2020). It suggests that measures should be expanded and include child neglect, especially emotional neglect, in future studies.…”
Section: Discussion and Application To Practicementioning
confidence: 99%
See 3 more Smart Citations
“…Parent group sessions indicated that parents did not realize that they should show or tell children that they love them and the impact of not doing so before they attended the program. Previous studies have shown that neglect, especially emotional neglect, is among the most prevalent types of child maltreatment in China (Wang, Cheng, et al, 2020; Wang, Wong, et al, 2020). It suggests that measures should be expanded and include child neglect, especially emotional neglect, in future studies.…”
Section: Discussion and Application To Practicementioning
confidence: 99%
“…Child maltreatment is a global public health issue affecting the well-being of millions of children (Stoltenborgh et al, 2014). In China, although harsh and controlling parenting strategies are declining in the current generation of parents, physical discipline is still considered beneficial for children's future (Qiao & Chan, 2005; Wang, Cheng, et al, 2020; Wang, Wong, et al, 2020). The prevalence of child physical abuse in China was estimated at 36.6% (Ji & Finkelhor, 2015), which was significantly higher than the international and Asian estimates in a study by Stoltenborgh et al (2013).…”
mentioning
confidence: 99%
See 2 more Smart Citations